Proposal Of Effective Maintenance Plan For Enhancing Overall Equipment Effectiveness At Palm Oil Mill - Ibrahim, Jamadeel Izwan (2019)
Every company, be it manufacturing or service-oriented will be looking for its best ways to improve profits without increasing the business capital. The management team will work at their best to think and execute any alternatives that can increase productivity at the same time having the concept that can save cost, time and energy. It is undeniable that machines have contributed a lot to increasing productivity, but if it is not well-maintained, it will not serve the purpose. This study emphasizes reducing the downtime in Kilang Sawit Kota Bahagia (KSKB) Palm Oil Mill caused by the breakdown of the production. The downtime data for the year 2017 showed that downtime has increased from January until December especially during the months of July, August, October and November where the hours of downtime were 10, 15.5, 15 and 15 hours respectively . The objective of this study is to identify the potential causes of the downtime by using the Ishikawa Diagram and Pareto Chart. Additionally, the performance of the machines related was assessed using Overall Equipment Effectiveness (OEE) Analysis. The Total Productive Maintenance (TPM) method was proposed to overcome the downtime problem with the implementation of S, Planned Maintenance and Autonomous Maintenance for two months of the trial period. Finally, the proposed method was evaluated and the result indicated that there was an increment of machine’s OEE for example; screw press machines from 6.4% to 30.5%.